2005
DOI: 10.1002/art.21539
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of anti–ribosomal P protein antibody testing for the diagnosis of neuropsychiatric systemic lupus erythematosus: An international meta‐analysis

Abstract: Objective. To quantitatively evaluate the diagnostic accuracy of antibodies to ribosomal P proteins (anti-P) for neuropsychiatric systemic lupus erythematosus (NPSLE) in general, for psychosis, mood disorder, or both, and for other diffuse manifestations.Methods. This international meta-analysis combined standardized data from 1,537 lupus patients contributed by 14 research teams. Weighted estimation of sensitivity and specificity with fixed-effects and random-effects models, as well as summary receiver operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
2
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(117 citation statements)
references
References 50 publications
1
106
2
8
Order By: Relevance
“…With regard to autoantibodies, the current data suggest that aPL cause focal NP disease (e.g., stroke, seizures) by promoting intravascular thrombosis (5). In contrast, anti-P antibodies (21,22), and possibly anti-NR2 antibodies (13,15), cause diffuse NP events (e.g., psychosis, depression, cognitive impairment) through a direct effect on neuronal cells; a critical factor in this is the ability of these antibodies to directly access neuronal cells either through intrathecal production or via passage from the circulation across a permeabilized blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to autoantibodies, the current data suggest that aPL cause focal NP disease (e.g., stroke, seizures) by promoting intravascular thrombosis (5). In contrast, anti-P antibodies (21,22), and possibly anti-NR2 antibodies (13,15), cause diffuse NP events (e.g., psychosis, depression, cognitive impairment) through a direct effect on neuronal cells; a critical factor in this is the ability of these antibodies to directly access neuronal cells either through intrathecal production or via passage from the circulation across a permeabilized blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The most direct evidence supporting the hypothesis of autoantibody involvement in NPSLE is derived from studies of animal models (13)(14)(15)(16)(17), whereas evidence from human studies is frequently conflicting or inconclusive (18)(19)(20)(21)(22). This may be due in part to methodologic difficulties involving, for example, selection of patients for study, lack of rigor in the characterization of NP events, and differences between laboratories in assay techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 However, large clinical studies and meta-analyses have reached variable results with regard to the presence of antiribosomal P antibodies in neuropsychiatric SLE, with differences attributed to laboratory methodology, study population, fluctuating course of disease, and diagnostic discrepancies. 47,48 Other groups have reported that a subset of anti-DNA antibodies in SLE cross-react with NMDA receptors, potentially resulting in neuropsychiatric abnormalities. 49 In contrast with anti-NMDA receptor encephalitis, the autoantibodies in SLE recognized the NR2A and NR2B subunits of the NMDA receptor, 49 which are developmentally regulated and highly expressed in hippocampus.…”
Section: Encephalopathy In Lupus and Other Systemic Syndromesmentioning
confidence: 99%
“…Se encuentran de 5% a 13% de los pacientes con LES. Son específicos de LES, y se han relacionado con LESNP en globo (psicosis lúpica y trastornos depresivos), pero con una potencia predictora dé-bil 21,34,[44][45][46][47][48] . Recientemente, Matus et al, trabajando en nuestro laboratorio, identificaron un autoanticuerpo proveniente de una paciente con psicosis lúpica dirigido contra un antígeno P ubicado en la superficie neuronal (llamado NSPA por sus siglas en inglés), reconocido por autoanticuerpos anti-P 49 .…”
Section: Autoanticuerpos En Lesnpunclassified